Association of excessive smartphone use with psychological well-being among university students in Chiang Mai, Thailand - Arunrat Tangmunkongvorakul (2019)
© 2019 Tangmunkongvorakul et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background Despite the pervasive use of smartphones among university students, there is still a dearth of research examining the association between smartphone use and psychological wellbeing among this population. The current study addresses this research gap by investigating the relationship between smartphone use and psychological well-being among university students in Thailand. Methods This cross-sectional study was conducted from January to March 2018 among university students aged 18–24 years from the largest university in Chiang Mai, Thailand. The primary outcome was psychological well-being, and was assessed using the Flourishing Scale. Smartphone use, the primary independent variable, was measured by five items which had been adapted from the eight-item Young Diagnostic Questionnaire for Internet Addiction. All scores above the median value were defined as being indicative of excessive smartphone use. Results Out of the 800 respondents, 405 (50.6%) were women. In all, 366 (45.8%) students were categorized as being excessive users of smartphones. Students with excessive use of smartphones had lower scores the psychological well-being than those who did not use smartphone excessively (B = -1.60; P < 0.001). Female students had scores for psychological well-being that were, on average, 1.24 points higher than the scores of male students (P < 0.001). Conclusion This study provides some of the first insights into the negative association between excessive smartphone use and the psychological well-being of university students. Strategies designed to promote healthy smartphone use could positively impact the psychological wellbeing of students.